An introduction to Error Control Coding - Imtawil, Dr.virasit (Engineering and Applied Science Research, 2013)
This paper provises an introduction to Error Control Coding (ECC) widely used in digital communication and storage systems. ECC was widely used in digital communication and storage systems. ECC was discovered in 1950 after a great scientist named C.E. Shannon published his paper titled “A Mathematical Theory of Communications” in 1948 in which he theoretically showed we can make an error-free communication system given a suitable design of encoding and decoding processes. However, he did not tell us how to achieve such a great system in practice. This has made many researchers worldwide interested in the paper and trying to get to this goal since. ECC is fundamentally based on the addition of redundancy to the digital data in order to protect the data from noise and interference. The process of determining this redundancy makes a variety of encoding methodologies.